ANALISIS METODE RESITASI TERHADAP HASIL BELAJAR BAHASA INGGRIS PESERTA DIDIK KELAS IV MI FUTUHIYYAH MRANGGEN DEMAK - Septi Audia Sukma; Muhammad Arief Budiman (STKIP Subang, 2023)
The purpose of this study is to describe the application of the recitation method to English lessons, the advantages of using the recitation method in English lessons and the obstacles found in applying the recitation method to English lessons. This research uses a descriptive qualitative approach. The research location is MI Futuhiyyah Kab. Demak Kec, Mranggen. The subjects in this study were English teachers and fourth grade students at MI Futuhiyyah. The data collection techniques used were tests, observations, in-depth interviews and questionnaires. The results showed that the application of the recitation method to English lessons was carried out from the phases of giving assignments, implementation and accountability of assignments that had been made. learning so as to minimize getting a score under the KKM. The average score obtained by students is 70 and the KKM for English is 70. The conclusion obtained is that during learning it proves that students understand learning English using the recitation method.